Imitation and social learning in robots, humans and animals behavioural, social and communicative dimensions - Nehaniv, Chrystopher L. 1963-; Dautenhahn, Kerstin 1964- (Cambridge University Press, 2007)
Mechanisms of imitation and social matching play a fundamental role in development, communication, interaction, learning and culture. Their investigation in different agents (animals, humans and robots) has significantly influenced our understanding of the nature and origins of social intelligence. Whilst such issues have traditionally been studied in areas such as psychology, biology and ethnology, it has become increasingly recognised that a 'constructive approach' towards imitation and social learning via the synthesis of artificial agents can provide important insights into mechanisms and create artefacts that can be instructed and taught by imitation, demonstration, and social interaction rather than by explicit programming. This book studies increasingly sophisticated models and mechanisms of social matching behaviour and marks an important step towards the development of an interdisciplinary research field, consolidating and providing a valuable reference for the increasing number of researchers in the field of imitation and social learning in robots, humans and animals
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Robotics; Robots / Control systems; Nachahmung; Organismus; Humanoider Roboter; Aufsatzsammlung